Financing higher education students in Malaysia using Islamic student loan-backed securitization: an empirical analysis / Shafinar Ismail … [et al.] - Ismail, Shafinar; Bakri, Mohamed Hariri; Ali, Rosalan; Md Noor, Azman (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The introduction of Asset-Backed Securitization (ABS) in Malaysia has benefited the economy. Though only spanning over twelve years, the securitization process and its continuous innovation have contributed to resolving and risk managing problems. We particularly focus herein on the student loan problem, which has not yet been implemented as a securitization process in Malaysia. The main purpose of this research is to investigate the possibility of Islamic student loan-backed securitization (i-SLBS) to be implemented in Malaysia. This framework is proposed to create a structure of i-SLBS and therefore, issue a highly graded and marketable sukuk that complies with global shariah principles, and hence, help the Malaysian government to produce high income nation with high labour skill and qualification. The proposed cash flow shows that student loans can be sustained and self-funded by 2038. The expectation is that the new financial instrument will benefit both the students and the government.